Prognostic analysis for Chinese patients with stage I ovarian endometrioid carcinoma - Yu Zhao; Shu Wang; Yi-Min Qu; Yu-Ting Ji; Keng Shen; Jing He Lang (BMC, 2017)
Abstract Background This study aimed to identify the clinical and pathological characteristics and the possible prognostic factors for Chinese patients with early-stage ovarian endometrioid carcinoma. Methods The present study reviewed the medical records of patients who received initial treatment and a postoperative pathological diagnosis of ovarian endometrioid carcinoma at our center. In all, 78 patients had stage I ovarian endometrioid carcinoma. Results In this series, the 5-year overall survival rate and 5-year disease-free survival (DFS) rates of patients with stage I ovarian endometrioid carcinoma was 98.7% and 87.2%, respectively. Univariate analysis showed the factors that influence the DFS rates include menopausal status, FIGO stage, histological grade, lymphadenectomy, cytology of ascites. Multivariate analysis showed that grade 3 and lymphadenectomy were the independent prognostic factors of DFS for Stage I ovarian endometrioid carcinoma (P = 0.0259, 0.0276 respectively). However, the coexisting endometriosis, concomitant endometrial disorders, dissection of para-aortic lymph node and more courses of thermotherapy had no influence on DFS. Besides, it was found that 19.3% of patients in this series had synchronous early stage and well-to-moderate differentiated endometrial carcinoma. Conclusions Grade 3 and lymphadenectomy were indicated as the independent factors of DFS for stage I patients with ovarian endometrioid carcinoma. The endometrial changes should be considered seriously when fertility-sparing surgery was planned.